ReactJS 18, Firebase 9 project-realtor clone. (Packt Publishing, 2023)
This is the best course to learn React.js, Firebase, and Tailwind CSS by creating a real estate website. In this course, you are going to learn how to build a realtor clone using ReactJS version 18, Firebase version 9, and Tailwind CSS version 3. In this course, we are going to create a stunning new listing section, custom categories, responsive design, listing cards, rent and sale pages, and, most importantly, listing pages where you can see the map and image slider. Realtor clone is the best modern fully functional real estate application that you can currently find. By building this single web app, you will gain the knowledge needed to build any website that uses CRUD operations including CRUD functions in React using Firebase Firestore database. You will learn Firebase auth for complete authentication and learn how to sign up or sign in the users using username and password and Google oAuth. Also, we will add the Forgot Password functionality using Firebase auth to let the users get an email with the link to change their password. You will learn how to style the project using Tailwind CSS, including how to add custom classes. And finally, we will deploy the website to Vercel to be able to share it with others or put it on your portfolio. By the end of the course, you will learn to build a realtor clone using ReactJS version 18, Firebase version 9, and Tailwind CSS version 3. What You Will Learn Create a ReactJS project from scratch Use Firebase Firestore to store and fetch data Learn how to create pages and routes in a React project Learn how to create a beautiful spinner and loader Create a reusable component such as listing cards Learn to create private route and custom hook for protecting the user profile page Audience This course can be taken by React developers who want to have a portfolio project or by programmers who have a basic knowledge of HTML, CSS, and JavaScript. About The Author Dr. Sahand Ghavidel: Sahand Ghavidel holds degrees in Mathematics, Electrical, and Computer Science, and has earned a doctoral degree from Faculty of Engineering and IT, University of Technology Sydney. He has researched for more than a decade about artificial algorithms and optimization. He has won several awards for his outstanding research and has published more than 40 ISI journals and attended many international conferences. The number of people using and citing Sahand's publications is significantly high which is more than 1600 citations, according to Google scholar (April, 2021). He was also awarded the outstanding reviewer in the "International Journal of Electrical Power & Energy Systems" with CiteScore of 5.79 in recognition of his contributions added to the quality of the journal. Sahand has more than 15 years of programming experience. The first programming language he learned was visual basic when he was just 12 years old. Since then, he has made hundreds of websites, and apps with different programming languages like JavaScript and Python.